Across Functional Boundaries: Making Nonneutralizing Antibodies To Neutralize HIV-1 and Mediate Fc-Mediated Effector Killing of Infected Cells - Jonathan Richard (American Society for Microbiology, 2021)
Highly conserved epitopes within the coreceptor binding site (CoRBS) and constant region 1 and 2 (C1-C2 or cluster A) are only available for antibody recognition after the HIV-1 Env trimer binds host cell CD4; therefore, they are not accessible on virions and infected cells, where the expression of CD4 is downregulated. Here, we have developed new antibody fusion molecules in which domains 1 and 2 of soluble human CD4 are linked with monoclonal antibodies of either the CoRBS or cluster A specificity.